Um breve histórico das araras do gênero Anodorhynchus Spix, 1824 (Aves, Psittaciformes) - Nelson Papavero; Dante Martins Teixeira (Arquivos de Zoologia, 2016)
Since the Antiquity, parrots, parakeets and their relatives (Psittacidae) aroused a great interest in Europe, both for their colours as for their notorious capacity of interacting with human beings. With the discovery of the Americas, new species would be introduced in the traffic of exotic animals a long time ago established by Europeans with Africa and the East. Effectively, even before Columbus finished his fourth and last voyage (1502-1504), neotropical parrots had already made their appearance in chronicles, in the cartography and the fine arts. Although the oldest notices about blue macaws of the genus Anodorhynchus date from the end of the 16th century, and the first image from the beginning of the 17th century, those birds would be better known by Europeans only in the second half of the 18th century. In a general way, the sources examined herein proved to be especially significant for Anodorhynchus glaucus, as all the first hand information about the biology and the behavior of this macaw are registered in testimonies prior the 20th century. It is not impossible to suppose, therefore, that further details about this species and a better understanding of its mysterious disappearance could be obtained from the perusal of the vast documentary collection about the Rio de la Plata basin left by Jesuits, as well as from a more accurate reading of the reports by travelers and naturalists which, such as Friedrich Sellow and Auguste de Saint Hilaire, journeyed through Argentina, Paraguay, Uruguay, and southern Brazil.